Evidence-based semiquantitative methodology for prioritization of foodborne zoonoses36823 - S. Cardoen; Van Huffel,X.; Dirk Berkvens; Sophie Quoilin; Ducoffre,G.; Saegerman,C.; Niko Speybroeck; Hein Imberechts; Herman,L.; R. Ducatelle; Katelijne Dierick (Foodborne.Pathog.Dis., 2009)
OBJECTIVES: To prioritize an extended list of food- and water-borne zoonoses to allow food safety authorities to focus on the most relevant hazards in the food chain. METHODS: An evidence-based semiquantitative methodology was developed. Scores were given by 35 scientific experts in the field of animal and public health, food, and clinical microbiology and epidemiology to 51 zoonotic agents according to five criteria related to public health (severity and occurrence in humans), animal health (severity of disease coupled with economic consequences and occurrence in animals), and food (occurrence in food). The scoring procedure was standardized and evidence-based as experts were provided, for each zoonotic agent, a same set of up-to-date help information data related to the five criteria. Independently, the relative importance of the five criteria was weighted by seven food chain risk managers. The zoonotic agents were ranked based on overall weighted scores and were grouped in four statistically different levels of importance. RESULTS: The following foodborne zoonotic pathogens were classified as "most important": Salmonella spp., Campylobacter spp., Listeria monocytogenes, and verocytotoxigenic Escherichia coli. A second group of "significant importance" included Toxoplasma gondii, the agent of bovine spongiform encephalopathy, Clostridium botulinum, Staphylococcus aureus, Cryptosporidium parvum, Mycobacterium bovis, Echinococcus granulosus, Streptococcus spp., Echinococcus multilocularis, Yersinia enterocolitica, Mycobacterium avium, Fasciola hepatica, Giardia intestinalis, and Rotavirus. CONCLUSIONS: This methodology allowed to rank 51 zoonotic agents with objectivity and taking account of a combined input from risk assessors and risk managers. APPLICATIONS: These results support food safety policy makers to establish the multiannual monitoring program of foodborne zoonoses. They also enable to identify knowledge gaps on specific zoonotic agents and to formulate key research questions. Principally, this method of prioritization is of general interest as it can be applied for any other ranking exercise and in any country
Keywords: 0; a; Agent; Agents; an; Animal; Animals; application; applications; article; AS; bacteria; Belgium; Blood-Borne Pathogens; bovine spongiform encephalopathy; Brussels; Campylobacter; classification; Clinical; Clostridium; Clostridium botulinum; consequences; Control; Countries; criteria; data; Databases,Factual; disease; Echinococcus multilocularis; ECONOMIC; electronic; epidemiology; Escherichia coli; Establish; evidence based; evidence-based; Evidence-Based Practice; Exercise; Field; food; Food Chain; Food Microbiology; Food Parasitology; Food Safety; Foodborne Diseases; general; Group; hazard; health; Health Priorities; Help; Human; Humans; identify; im; INFORMATION; IS; IT; journal; KNOWLEDGE; LEVEL; levels; List; Listeria; Listeria monocytogenes; method; methodology; methods; microbiology; Monitoring; Mycobacterium; Mycobacterium bovis; objectives; occurrence; ON; Parasites; pathogen; pathogenicity; POLICIES; POLICY; prion; Prions; PROGRAM; public; public health; Public-health; questions; Ranking; relative; Research; Research Support; result; results; risk; SAFETY; Salmonella; SB - IM; Score; severity; specific